DETERMINATION OF CHANGES IN THE CONTENT OF PRO- AND ANTI-INFLAMMATORY CYTOKINES IN PATIENTS WITH TRUE AND MICROBIAL ECZEMA - Dashchuk, A.А.; Dashchuk, A.M.; Fomina, L.V.; Dobrzhanska, Ye.I. (World of Medicine and Biology, 2024)
The widespread, long-term chronic course of the disease, the complex nature of the disorders and insufficiently studied pathogenesis determine the interest in the problem of eczema. The purpose of this study was to study the features of changes in the content of peripheral blood interleukins depending on the clinical course, severity and duration of eczema to determine the role of the identified disorders in the development of the inflammatory process. In 40 patients with true and microbial eczema, anamnestic and clinical features, the nature of the disease, as well as the use of highly sensitive ELISA determined the features of cytokine status depending on the selected parameters. These features of cytokine imbalance, which depend on the clinical manifestations of dermatosis, suggest their role in the development of exudative-destructive process in eczema. The concentration of IL-2 in both groups decreased, and IL-4 increased, more pronounced in the 2nd group. The revealed disorders in microbial and true eczema of the level of pro- and anti-inflammatory IL, and the correlation of interleukin parameters have pathogenetic significance and determine the features of the clinical course of this disease.
Keywords: true eczema; microbial eczema; immune system; cytokines; pathogenesis of eczema